Elaboração de manual de eficientização energética para aplicação em micro e pequenas empresas comerciais varejistas - Freitas, José Abilio Lima de (2009)
This dissertation brings a plan for improvements in the form of a technical manual on combating waste electrical energy in micro and small enterprises commercial retailers, energy of diagnosis-based microenterprises and small commercial enterprises retailers Santa Maria- RS. Thus, technical manual enables to micro and small enterprises, eficientization actions and strategies, as well as the determination of the magnitude of the results of actions proposed eficientization. The data were addressed quantitatively, through statistical methods, whose results represent the entire population of firms in the study. The results show the potential of separate technical topics eficientization (accounts and supply, lighting, cooling, and other equipment), as well as the total eficientização potential. Joint analysis of all topics, for the entire population of micro and small enterprises in study identified in waste, reaching 13.5% in micro companies and 11.6% in small companies. These figures represent the greatness of electrical energy wastage in enterprises, and justify the preparation of the plan of improvements to the energy eficientization, which contributes to the knowledge of electricity companies on the subject, motivating the change of attitude with regard to combating waste this white paper, reducing production costs, as well as increased quality and productivity of their products and/or services, favouring competitiveness and ensuring their survival on